Potencialidades para o desenvolvimento do geoturismo no Município de Itapipoca (CE) - Machado, Ricardo Matos (2018)
Since the United Nations Conference on the Human Environment held in Stockholm (1972), an environmental awakening has been observed in society, where the biotic environment has been valued and the term biodiversity has spread globally. However, it is only from the 1990s onwards that an awakening to the valorization of the abiotic environment, which forms the basis for all forms of life, is achieved, making the terms Geodiversity, Geoconservation, Geoheritage, Geopark and Geotourism, gaining space in geosciences. From this point of view, the work was developed in Itapipoca, Ceará, which has an environmental peculiarity due to the fact that it has three distinct environments: the coast (coastal plain), the sertão (sertão) and the serra (residual mass of Uruburetama), a characteristic that led him to be known regionally as the "Land of Three Climates". Geotourism, which focuses more on the physical environment (abiotic) and, in many cases, seeking to meet sustainability precepts that ecotourism has not reached, offers, through its practices, the possibility of carrying out basic tourism sustainable, geared to endogenous economic development and that has an instructive, educational, sensitizing and promising character of local sustainability. However, some questions arise: do geodiversity elements present in the municipality of Itapipoca have exceptional scientific and / or tourist values to the point of being classified as geosites? And if they present, what are their potentialities and vulnerabilities? From these premises, it was established the general objective of the research that is to analyze the potentialities for the development of geotourism in the municipality of Itapipoca. For the inventory of points, the qualitative method adopted was adapted from Pereira (2006), where the sites of geomorphological interest were the components of the landscape used as parameters for the exaltation of the components of the local geodiversity. As a subsidy for territorial planning and management, a route of Geotourism Potentialities for the municipality of Itapipoca was proposed based on the methodology of Sell (2017), which contemplates different environments and their components more detachable from the point of view of geodiversity and geoconservation, as well as from the geographical, tourist and / or scientific point of view. The characterization of the landscape followed by the geosystemic bias, and due to the environmental characteristics pertinent to the municipality treated here, the present work has as a precept to serve as an aid in the popularization of the knowledge about the abiotic resources, realizing the valorization / divulgation of the components of the physical environment of the Itapipoca landscape, characterizing the physical structuring of the landscapes present there, as well as, exalting its potential for the practice of Geotourism, treated here as an incentive tool for sustainable and promising endogenous development. environmental education.